PENINGKATAN PEMAHAMAN JEMAAT KAUM BAPAK GKSI GLORIA BANING TERHADAP PERTUMBUHAN KEROHANIAN ANGGOTA KELUARGA - Restu Gulo (Jurnal PKM Setiadharma, 2022)
Baning is a village located in Sekucing Labai Village, Simpang Hulu district, Ketapang district, west Kalimantan province. In this village stands the Gloria Baning Indonesian Faithful Christian Church. Based on observations made, some members of the GKSI Gloria Baning congregation understand that the duties and responsibilities of a husband are only to meet financial needs, some say that the spiritual needs of family members do not include the duties of the head of the household (each individual’s business), and some say that the duty and responsibility of preaching the gospel are only done by God’s servants (priests). This is what prompted this service activity to be carried out for the GKSI Gloria Baning congregation as an effort to increase the spirituality of those who were there. The method used by the author in writing this article is interviews and literature to support valid and comprehensive data. The results obtained after the activity was carried out showed a change in terms of; increasing knowledge and understanding and spirituality of the fathers about the duties and responsibility of the head of the family in the household and giving themselves part in the service on the Sunday service.